2018
DOI: 10.31018/jans.v10i1.1570
|View full text |Cite
|
Sign up to set email alerts
|

Response of drip irrigated Broccoli (Brassica oleracea var. italica) in different irrigation levels and frequencies at field level

Abstract: Abstract:Geometric increase in population coupled with rapid urbanization, industrialization and agricultural development are causing increased pressure on global water resources. Agriculture is the largest consumer of fresh water resources, thus the scope of enhancing water productivity in agriculture is taken to be the priority area of research. The right amount and frequency of irrigation is essential for optimum use of limited water resources for crop production as well as management. A field experiment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
3
5
0
Order By: Relevance
“…Lowest yield (12680 kg/ha in 2019-20 and 12830 kg/ha in 2020-21) was obtained at I 4 S. Similarly, the higher marketable yield (13960 kg/ha in 2019-20 and 14120 kg/ha in 2020-21) was found with I 2 SS treatment and lowest marketable yield was found at I 4 S (Table 1). These results are in close conformity with Kumari et al (2018) who found that irrigation after one day at 0.8 ET c showed a significantly higher total yield of broccoli. The significantly higher IWUE and FUE were recorded under I 2 SS and lowest was obtained in the treatment I 4 S during both seasons.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Lowest yield (12680 kg/ha in 2019-20 and 12830 kg/ha in 2020-21) was obtained at I 4 S. Similarly, the higher marketable yield (13960 kg/ha in 2019-20 and 14120 kg/ha in 2020-21) was found with I 2 SS treatment and lowest marketable yield was found at I 4 S (Table 1). These results are in close conformity with Kumari et al (2018) who found that irrigation after one day at 0.8 ET c showed a significantly higher total yield of broccoli. The significantly higher IWUE and FUE were recorded under I 2 SS and lowest was obtained in the treatment I 4 S during both seasons.…”
Section: Resultssupporting
confidence: 92%
“…When the field is irrigated less frequently, water can permeate deeper levels, whereas more frequent irrigations keep water in the upper layers (Chaharmahali et al 2022). On the basis of maximum yield of broccoli, Kumari et al (2018) also predicted the optimum moisture content under once in two days irrigation frequency with 80% of ET c . The soil water content is one of the most important factors which has direct impact on fruit yield (Ismail et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…All these contributory factors might have stimulated enhanced physiological processes, active cell division and photosynthetic activities of plants [ 13 ]. The dramatic decline in curd yield in drip irrigation at 0.6 ETc was mainly due to acute soil water stress-causing reverse osmosis in plants and was unable to replenish the crop water requirement [ 38 , 39 ]. Surface irrigation, on the other hand, rendered extensive wetting zone as water spreading over the large area due to high hydraulic gradient causing higher soil evaporation, excessive losses of water and nutrients in deep percolation, chocking of soil aeration in first few days immediately after irrigation, higher soil water stress between two successive irrigation and in some critical growth period and reduced nutrient availability due to heavy irrigation load which ultimately proved to be detrimental for a drastic reduction of crop growth and yield [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 90% of it is water, 2% is dietary fibre, 3% is protein, 5% is carbs, antioxidants, phytochemicals, vitamins A, B, and C, as well as minerals (Rodrigues et al, 2013). According to Kumari et al (2018), broccoli is susceptible to water stress and needs up to 4.1 mm of water per day. Due to the population's fast development, which needs increased food production and puts strain on these resources, there are growing worries about the world's threatened water and land resources (Islam and Mollah, 2014).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%